Mechanical properties of weightlifting bars - Chiu, L. Z. F. (The Journal of Strength and Conditioning Research, 2010)
Weightlifting training and competition involves lifting a revolving shaft bar loaded with weights. The design of a bar and the location of the weights result in bar deformation during lifting tasks. Because there are many manufacturers of weightlifting bars, the actual deformation of a bar may vary, depending on the steel alloys used. A modified 4-point static bending test was used to assess deformation of 8 weightlifting bars and 1 general purpose weight training bar. The apparent stiffness of the bars was determined by plotting bending moment vs. bar deformation (the vertical height difference between the center vs. ends of the bar). All bars tested had an absence of hysteresis during cyclic loading and unloading in 50-kg increments (up to 220-kg total barbell weight), demonstrating pure elastic properties. At maximum loading, bar deformation was 4-5 cm. A large range existed for apparent stiffness. Based on apparent stiffness calculations, recommendations are made for which bars are suitable for weightlifting training and competition. The deformable nature of weightlifting and weight training bars should be considered before their use in exercise, sport, or research.